2017
DOI: 10.1186/s12966-017-0572-1
|View full text |Cite
|
Sign up to set email alerts
|

Food parenting practices for 5 to 12 year old children: a concept map analysis of parenting and nutrition experts input

Abstract: BackgroundParents are an important influence on children’s dietary intake and eating behaviors. However, the lack of a conceptual framework and inconsistent assessment of food parenting practices limits our understanding of which food parenting practices are most influential on children. The aim of this study was to develop a food parenting practice conceptual framework using systematic approaches of literature reviews and expert input.MethodA previously completed systematic review of food parenting practice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 36 publications
1
57
0
1
Order By: Relevance
“…The use of both experts and parents to establish the content and scope of FPPs around snacking resulted in an instrument that likely covers all relevant constructs. This notion is further supported by other studies that aimed at identifying and defining FPPs constructs [ 17 , 36 , 37 ]. The recently published parenting around Snacking Questionnaire [ 38 ] also corroborates many of the constructs measured in the CSPQ.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The use of both experts and parents to establish the content and scope of FPPs around snacking resulted in an instrument that likely covers all relevant constructs. This notion is further supported by other studies that aimed at identifying and defining FPPs constructs [ 17 , 36 , 37 ]. The recently published parenting around Snacking Questionnaire [ 38 ] also corroborates many of the constructs measured in the CSPQ.…”
Section: Discussionsupporting
confidence: 66%
“…It showed that parents use parenting practices in combination, and that this complex interactional nature can be captured perfectly to predict children’s snack intake. Since we believe that the theoretical dimensions of food parenting practices currently proposed in the literature (e.g., autonomy support, coercive control, and structure) [ 17 , 36 , 37 ] do not fully account for this complex interactional nature of FPPs, we did not test an a priori formulated factor structure (i.e., structural validity) in our ongoing research on measurement properties of the CSPQ. We encourage the use of cluster analyses to further corroborate this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Participants have been students, teachers and parents in the same school (Haymovitz, Houseal‐Allport, Lee & Svistova, ) and parents, practitioners and administrators concerned about parent enrolment of children in preventive programs (Houle, Besnard, Berube & Dagenais, ). Topics range considerably, such as personal experiences of disability (Elsman, van Rens, Hermanus, Bartholomeus, van Nispen & Antoinette, ), practices of caregivers with children (O’Connor et al, ), and relationships and dating violence (Goldman, Mulford & Blachman‐Demner, ).…”
Section: Introductionmentioning
confidence: 99%
“…This questionnaire was developed after a thorough search of the literature and assesses five parenting constructs: nurturance, structure, behavioral control, overprotection, and coercive control [143]. Unfortunately, there is little consensus on how to best measure food parenting practices [198]. There are at least 71 instruments measuring food parenting practices [199].…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…In most cases, these instruments measure a small part of the spectrum of food parenting practices [199]. Fortunately, a comprehensive food parenting practices item bank is currently being developed, which will allow a more consistent and comprehensive measurement of food parenting practices in the future [198]. For the measurement of the family-level influence, we recommend the use of the FNC.…”
Section: Implications and Recommendationsmentioning
confidence: 99%